ANALISIS FAKTOR PENENTU VOLUME PENJUALAN PADA PERUSAHAAN KADOKAYUKU KABUPATEN SUMEDANG - Setiyowati Setiyowati; Fidyah Yuli Ernawati (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
The population in this study is the entire sales team at the Kadokayuku company, amounting to 400 people. Then the sample is drawn using the Slovin formula into 80 samples. The results of this study indicate that (1) there is an influence of distribution channels on sales volume. This can be seen from the tcount of 3.296> t table 1.991 or p-value = 0.001 <α 0.05. (2) there is no effect of price on sales volume. This can be seen from the tcount of 0.359 <t table 1.991 or p-value = 0.721> 0.05. (3) there is the effect of promotion on sales volume. This can be seen from the tcount of 2.283> t table 1.991 or p-value = 0.025 <0.05. (4) there is an influence of distribution channels, prices, and promotions that together have a positive and significant effect on sales volume. This can be seen from the value of fcount 13.909> ft. 2.72 and p-value <α or 0,000 <0.05. Distribution, price and promotion channels need to be considered, because based on the results of the study, the three variables together have a considerable influence on the sales volume of the Kadokayuku company by 32.9%. Based on the magnitude of the influence it is expected that Kadokayuku companies can increase the number of distribution channels, carry out more effective and innovative promotions and in determining the selling price of products, the company does not only pay attention to profits and cover production costs, but must also look at the selling prices of competing products in order to compete with prices selling other companies so that they can increase the sales volume of the Kadokayuku company.